The In-Class Flip Model In Teaching Speaking: Improving Elementary Students’ Skill And Learning Process - Adin Fauzi (Universitas Pendidikan Ganesha, 2020)
This study aimed to enhance the students’ speaking skill and the learning process of speaking by implementing the in-class flip model. The participants of this classroom action research were grade V students of an Islamic elementary school. There were six students who participated in this study. This study was conducted in one cycle consisting of two meetings. The data were collected through observation, interview, and rubric. The findings indicate that the students’ speaking skill improve after learning in the in-class flip model. Before this study, the students struggled with speaking. At the end of this study, the students perform better in speaking in the aspects of vocabulary, pronunciation, and structure. The learning process is student-centered thanks to group activities. The students are also more active, motivated, responsible, and cooperative during the learning process. This study concludes that the in-class flip model is effective to teach English to young learners.